Exploring the Effects of Psychological Factors on the Use of Navigation Systems While Driving - Ntasiou Nikoletta; Adamos Giannis; Nathanail Eftihia (Transport and Telecommunication, 2021)
The ever-increasing use of private vehicles makes Advanced Driver Assistance Systems (ADAS) more necessary as they improve users’ convenience, safety and travel time. Although these systems offer significant advantages, they call into question the traditional role of users, making the psychology of drivers towards these technologies a necessary factor for their adoption. The purpose of this paper is to investigate the effects of psychological factors on the use of one of the most widely used ADAS, the Global Navigation Satellite Systems (GNSS). Towards this direction, a literature review was conducted to identify the factors that influence drivers’ behavior and the psychology of drivers towards new technologies. Furthermore, a questionnaire survey was organized in Greece, based on the Theory of Planned Behavior, including additional variables, which were identified in the literature, such as technophilia, trust in technology and endorsement. From the data collected, models predicting the behavior of drivers were developed through structural equation modelling, concerning the use of navigation systems in both urban and interurban networks. The findings of the research reveal that the intention to use a navigation system is determined by various factors such as behavioral beliefs about its usage, normative beliefs and technophilia. The actual use of a navigation system depends to some extent on this intention.